Standardisation of magnetic nanoparticles in liquid suspension. (24th August 2017) - Wells, James; Kazakova, Olga; Posth, Oliver; Steinhoff, Uwe; Petronis, Sarunas; Bogart, Lara K; Southern, Paul; Pankhurst, Quentin; Johansson, Christer
Abstract: Suspensions of magnetic nanoparticles offer diverse opportunities for technology innovation, spanning a large number of industry sectors from imaging and actuation based applications in biomedicine and biotechnology, through large-scale environmental remediation uses such as water purification, to engineering-based applications such as position-controlled lubricants and soaps. Continuous advances in their manufacture have produced an ever-growing range of products, each with their own unique properties. At the same time, the characterisation of magnetic nanoparticles is often complex, and expert knowledge is needed to correctly interpret the measurement data. In many cases, the stringent requirements of the end-user technologies dictate that magnetic nanoparticle products should be clearly defined, well characterised, consistent and safe; or to put it another way—standardised. The aims of this document are to outline the concepts and terminology necessary for discussion of magnetic nanoparticles, to examine the current state-of-the-art in characterisation methods necessary for the most prominent applications of magnetic nanoparticle suspensions, to suggest a possible structure for the future development of standardisation within the field, and to identify areas and topics which deserve to be the focus of future work items. We discuss potential roadmaps for the future standardisation of this developing industry, and the likely challenges to be encountered along the way.